2010
DOI: 10.21608/jppp.2010.86963
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Effect of Some Inert Dusts Against Three of Stored Grain Insects at Kafr El-Sheikh Governorate

Abstract: Laboratory and field studies were conducted to evaluate the effect of three inert dusts, diatomaceous earth, kaolin and katelsous as wheat grain protectants against some stored grain insects, i.e., Sitophilus oryzae, Rhizopertha domininca and Tribolium confusum. Inert dusts were mixed with wheat grain in the laboratory at different concentrations. Data obtained from the laboratory experiment showed that the LC50, s of diatomaceous earth, kaolin and katelsous were 0.234, 0.071 and 0.235% w/w, 6.033, 6.306 and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Mewis and Ulrichs (2001) observed high mortality in Tribolium confusum, Plodia interpunctella, and Sitophilus granaries treated with low dosages of DE and found that it required a long exposure period to cause higher mortality. The results stand in the same line as El-Sayed et al (2010), who claimed that the treated wheat with diatomaceous earth highly reduced the population of Sitophilus oryzae, Tribolium castaneum, and Rhyzopertha dominica. Because of its low mammalian toxicity, worker safety, the low danger of food residues, and the formation of resistant insect populations linked to the use of chemical pesticides, diatomaceous earth usage has increased during the past decades.…”
Section: Discussionsupporting
confidence: 84%
“…Mewis and Ulrichs (2001) observed high mortality in Tribolium confusum, Plodia interpunctella, and Sitophilus granaries treated with low dosages of DE and found that it required a long exposure period to cause higher mortality. The results stand in the same line as El-Sayed et al (2010), who claimed that the treated wheat with diatomaceous earth highly reduced the population of Sitophilus oryzae, Tribolium castaneum, and Rhyzopertha dominica. Because of its low mammalian toxicity, worker safety, the low danger of food residues, and the formation of resistant insect populations linked to the use of chemical pesticides, diatomaceous earth usage has increased during the past decades.…”
Section: Discussionsupporting
confidence: 84%
“…are among the most DE-tolerant species, as T. castaneum was the least affected in comparison with the other three species as after the longest exposure time achieved 80% mortality at the highest concentration 10%(w/w), while S. oryzae was the most sensitive reached 100% mortality after 7days followed by O. surinamensis with 100% mortality after 7days, then S.paniceum with 94.4% mortality after 10 days at concentration of 10%(w/w)., so S. oryzae considered more susceptible than Tribolium spp. (Arthur, 2002;Athanassiou et al, 2003;Kavallieratos et al,2005;El-Sayed et al, 2010).…”
Section: Repellent Activitymentioning
confidence: 99%